Incorporating Digital Heritage Content Into Information Science Programs - Grzunov, Laura; Marjanović, Lela; Majstorović, Monika (Bobcatsss, 2023)
Information science is an area that does not actually have a generally accepted definition that everyone would agree with. The reason for this may be because the field itself is still considered relatively young, but also because it is strongly linked to other disciplines, such as information technology (IT). Information sciences follow and adapt to advances in technology that have become a very important support in their work. "In the 1990s, the Internet opened the door to information and communication, creativity and digital libraries in today's sense of the word" (Zubac & Tominac, 2012, p. 68). With the help of the Internet, or one of its parts - libraries through digitalization, storage and protection provide access to their own material. During their studies, information science students at the University of Zadar develop competencies necessary for building and managing collections of materials and information, information organization, design and provision of information services, research and analysis of information needs, problems and phenomena, organization and management of information institutions and networks, educational processes, cultural projects and scientific research, and training for lifelong learning. But is there a focus on digital libraries, the digital transformation, and the library profession of the future? Do students have the opportunity to participate in digitization and the creation of digital information services? The aim of the poster is to show the ways in which content related to all aspects of creating, collecting, processing and managing digital heritage is included in information science programs conducted at the Department of Information Science, University of Zadar, Croatia, and how information science students actively participate. in the creation of digital heritage content and their creative use. The active participation of students in the project Digitization, bibliographic processing and research of texts of the Zadar-Šibenik area until the end of the 19th century written in Glagolitic, Bosnian and Latin (further in text: Written Heritage) and their assignments on the project itself as an example of good practice. The phases of the project in which students participate will be described and explained with the aim of defining the competencies that students develop through the project and through courses related to digital libraries, digitization and digital transformation in general.